Exploring Gossip: Women Character Dynamics in Tilik the Series - Putri, Zahra Setia; Zahra, Aulia Nurussyifa Az; Lutfiana, Siti Fera Nur; Novita, Ratih; Ros, Gerry; Wijiastuti, Ayu; Annisa, Salsabila Farah Nur (Politeknik Harapan Bangsa Surakarta, 2024)
This article discusses the gossip practices of Muslim women in the film Tilik the Series. This study focuses on Muslim women to explore how they are represented in the media, especially in Indonesia, a country with a Muslim majority. In a culture influenced by Islam, religion shapes social norms and behaviors, including gossip. The film Tilik the Series depicts Javanese women, who are predominantly Muslim, although non-Muslim characters may not be prominently featured. This article aims to reveal how the process of gossip by women wearing the hijab is carried out as a storytelling tool and also plays a role in forming and maintaining social norms as well as revealing the types and functions of gossip among them. Apart from that, gossip in Tilik the Series is not just empty talk, every gossip practice has a different type and function, and each type and function can narrate the ins and outs of social life, which can be destructive and transformative. The method used is qualitative by identifying the relationship between types of gossip and function of gossip with the character of Muslim women. The conclusion is that the Muslim women in the film when gossiping tend to talk about the situation in their family environment or what we call the house-talk type. The gossip they do contains incitement so it can influence the opinion of the person they are talking to.